PRAGMATIC DISCOURSE ANALYSIS OF RELIGIOUS LANGUAGES FOR PEACE BUILDING AND SUSTAINABLE DEMOCRACY IN NIGERIA - ESTHER OLASUMBO OYEBANJO; PETER ADELAJA OYEBANJO (International Studies Journal)
The role of religious languages in promoting peace and supporting sustainable democracy cannot be over-emphasised. However, the language-specific strategies used by religious leaders to foster peace or democracy in the previous scholarships require a versatile discourse. This study pragmatically examined the influence of religious languages and their influences on the promotion of peace and sustainable democracy in Nigeria, with the view to providing insight into the potential of religious discourse as a tool for peace building and democratic stability within this context. This research employed a pragmatic discourse analysis approach and data were sourced from sermons, speeches, and public messages, focusing on speech acts, contextual implications, and intended meanings to better understand how religious language influences public perceptions. Religious languages often promote tolerance, forgiveness, and mutual respect, essential values for peace building in a pluralistic society. Religious leaders employ inclusive language, appeals to common values, and narratives emphasising social harmony to encourage peaceful coexistence. However, there are instances where religious messages, particularly those with political overtones or ambiguous wording, unintentionally reinforce divisions or fuel social tensions. As a result, there is the dual nature of religious discourse: its potential to either support or undermine democratic values and social unity. Therefore, it is imperative that religious leaders and policymakers collaborate to establish guidelines for effective religious communication that aligns with democratic ideals and peace-building objectives.